Cryopreservation of ram semen: Manual versus programmable freezing and different lengths of equilibration. (24th December 2021) - Vozaf, Jakub; Makarevich, Alexander V.; Balazi, Andrej; Vasicek, Jaromir; Svoradova, Andrea; Olexikova, Lucia; Chrenek, Peter
Abstract: The aim of our study was to examine effects of the length of semen equilibration as well as two freezing techniques on ram sperm post‐thaw quality. The ejaculates of Wallachian sheep rams ( n  = 12) were collected by an electro‐ejaculation, equilibrated in a Triladyl® (0, 2, 4, 6, and 8 h) containing glycerol and egg yolk and frozen by programmable freezing (PF) or manual freezing (MF). After thawing, sperm samples were subjected to the motility (computer‐assisted sperm analysis [CASA]), viability (SYBR‐14/PI), and fertilizing ability (FA) (in vitro penetration/fertilization test on bovine oocytes) assays. It was found that the equilibration of 6 h (E‐6) ensured higher post‐thaw sperm motility and progressive movement compared with other lengths tested, irrespective of a freezing technique. The E‐6 sperm viability did not differ between PF and MF but was lower ( P  < 0.05) than control. Sperm FA (E‐6) was similar in PF (60.44%) and MF (62%) but slightly lower than in fresh (72.8%). Our data demonstrate that the use of MF was comparable with PF, which can be applied in the field conditions without need in a piece of cost‐expensive equipment, which can greatly benefit the gene bank of animal genetic resources.